The protective effect of cinnamaldehyde on lipopolysaccharide induced acute lung injury in mice - Huang, H.; Wang, Y. (Cellular and Molecular Biology, 2017)
The study wasintended to examinethe protective effect of cinnamaldehyde (CM) on lipopolysaccharide (LPS)-induced acute lung injury (ALI) mice model.The results of the investigation confirmed that, LPS induced inflammatory cytokines such as TNF-Î±, IL-6, IL-13 and IL-1Î² were significantly decreased by CM. CM also up-regulated level of IL-10. We found that CM significantly attenuated LPS-induced TLR4 expression, NF-ÎºB activation and MPO activity in the lung tissues. It markedly reduced lung wet/dry ratio, and improved typical and severe pathological changes including pulmonary edema in the LPS induced ALI mice. Moreover, CM significantly inhibited neutrophils, macrophages and total cell number in the bronchoalveolar lavage fluid (BALF). In our study, we noted that TLR4–NF-ÎºB signaling pathway was involved in acute lung injury.The results revealed the protective effects of CM in LPS-induced ALI, through suppressionTLR4–NF-ÎºB signaling pathway. Our finding suggests that Cinnamaldehyde is a potential anti-inflammatory agent in treatment the acute lung injury.